THE FLOW OF PROPERTY AS A BASIS OF INTERNAL CONTROL. - Hord, Warner H. (The Accounting Review, 1939)
This article discusses various elements of accounting theory and practices which appear to be somewhat clarified when interpreted in terms of the transaction basis of internal accounting. This discussion has served to focus attention upon both the importance of accountancy and the extreme difficulty of many of the problems with which it must deal. It appears wholly unlikely that the various elements of accounting practice, as developed in separate business units, can ever be reduced to a single consistent body of principles. As all accounting is based upon the dual concept of property, which refers property as a thing of value to the business is an "asset", and property as an ownership right to such thing is an "equity." The amounts of the two are essentially equal, they are simply different aspects of the same thing. It is suggested that accounting assets and equities can respond only to the transaction flow of actual business properties and although the accounting equities may usually be summarized in terms of the legal equities, they cease to be accounting equities the moment they reflect legal rather than accounting changes in amounts if the two are in conflict. Thus there comes into existence a technical accounting concept embracing only the things, called assets; while simultaneously there comes into existence a second technical accounting concept embracing only the ownership claims to these things, called equities.